Eliminating world poverty : a challenge for the 21st century - Short, Clare (Stationery Office LondonGB, 1997)
Sets out the British government's policies to achieve the sustainable development of this planet. Focuses on eliminating poverty. Looks at four aspects viz. the challenge of development; building partnerships; consistency of policies; and, building support for development.